Readings of “Hum dekhenge” by faiz ahmed faiz. Islamic images, revolution, or anti-Hindu sentiments? - Meagher, G.C. (Estudios de Asia y Africa, 2021)
This article examines the controversy caused by the Faiz Ahmed Faiz’s poem “Hum Dekhenge” during the protests triggered by the approval of the Citizenship Amendment Act and the National Registry of Citizens at the end of 2019 in India. In addition to a Spanish translation of the actual text, it also offers a background of the debate, a biographical sketch of the poem’s author, and diverse interpretations. The production of meaning is a complex articulation between text, readers, and the sociopolitical context. “Hum Dekhenge” is a poem of various linguistic, literary, and political registers. Without question its reading is open to multiple possibilities. © 2021. Estudios de Asia y África.
Keywords: dept.wll